An observational study of technical and non-technical skills in advanced life support in the clinical setting - Peltonen Ville; Peltonen Laura-Maria; Salanterä Sanna; Hoppu Sanna; Elomaa Jaana; Pappila Tomi; Hevonoja Eeva; Hurme Saija; Perkonoja Katariina; Elomaa Teemu; Tommila Miretta (Elsevier, 2022)
Objective
Technical skills (TS) and non-technical skills (NTS) are the primary elements ensuring patient safety during advanced life support (ALS) and effective crisis resource management (CRM). Both skills are needed to perform high-quality ALS, though they are traditionally practiced separately. The evidence of the association between NTS and TS in high-quality ALS performance is insufficient. Hence, we aimed to evaluate the association between the skills in real-life in-hospital ALS situations.
Methods
We video recorded real-life in-hospital ALS situations, analyzed TS and NTS demonstrated in them with an instrument measuring TS and NTS, and tested the linear association between NTS and TS using a linear mixed model.
Results
Among 50 real-life in-hospital ALS situations that we recorded, 20 had adequate data for analysis. NTS and TS total scores were associated with one another (slope 0.48, P < 0.001). All NTS subcategories were associated with the TS total score (slopes ranging from 0.29 to 0.39, P < 0.001). The NTS total score and TS subcategories (chest compression quality, ventilation quality, rhythm control and defibrillation quality) were associated with one another (slopes ranging from 0.37 to 0.56, P < 0.01).
Conclusions
The resuscitation teams who demonstrated good NTS also performed the technical aspects of ALS better. The results suggest that NTS and TS have an association with one another in real-life in-hospital ALS situations. NTS performance had the most evident association with chest compression quality and rhythm control and defibrillation quality; these are considered the most crucial elements affecting outcomes of ALS. The findings of the study present novel information of what and why to emphasize in ALS training.
Clinical trial registration. ClinicalTrials.gov, NCT03017144.